ADOPTION OF PEER-TO-PEER (P2P) FINTECH LENDING : A STUDY OF SOCIO-DEMOGRAPHIC FACTORS - Rayenda Khresna, Brahmana; Evan, Lau (UNIMAS Publisher, 2024)
This research examines the socio-demographic factors of Peer-to-Peer (P2P) fintech lending within the Indonesian context. This research takes three different P2P Fintech lending measures: total fintech accounts, total fintech transactions, and total fintech loan disbursement. Using provincial data from 2019 to 2022, our robust panel regression found that education, internet literacy, poverty, and gender play important roles in P2P Fintech lending, specifically the total accounts and transactions. However, the total fintech loans were only determined by education and Gender. This study contributes significantly to the digital economy literature, specifically within the fintech domain, offering valuable insights for policymakers and financial authorities in Indonesia to enhance regulatory frameworks and foster a more inclusive P2P Fintech landscape